Preparation process of GL80 silicon-aluminum alloy

By performing multiple remelting in the silicon-aluminum alloy preparation process and using composite deterioration agents for deterioration treatment, the problems of uneven composition and unstable mechanical properties in the silicon-aluminum alloy preparation process are solved, and efficient preparation of alloys and improvement of mechanical properties are achieved.

CN119530627APending Publication Date: 2025-02-28JIANGSU HUANENG ENERGY SAVING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411738642.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing silicon-aluminum alloy preparation process has problems such as uneven alloy composition, unstable mechanical properties, high production costs, and complex processes.

Method used

A GL80 silicon-aluminum alloy preparation process is adopted. By remelting silicon powder and silicon-aluminum alloy 2-3 times, adding composite deterioration agent for deterioration, including rare earth salt, sodium fluorosilicate, sodium phosphate and aluminum powder, stirring and refining, and finally casting and molding.

Benefits of technology

Through this process, the crystalline silicon structure can be refined, the mechanical properties of the alloy can be improved, the stability and density of the material can be enhanced, and the production cost can be reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162097170000061
    Figure BDA0005162097170000061
  • Figure BDA0005162097170000071
    Figure BDA0005162097170000071
Patent Text Reader

Abstract

The invention relates to the technical field of metal preparation, and particularly discloses a preparation process of a GL80 silicon-aluminum alloy. When the silicon-aluminum alloy is prepared, a melting casting technology is adopted, after silicon-aluminum alloy raw materials and silicon powder are remelted for multiple times in the nitrogen atmosphere, a composite modifier is added for modification treatment, refining and impurity removal are conducted after stirring, and finally casting forming is conducted. Wherein the composite alterant is prepared by mixing rare earth salt, sodium fluosilicate, sodium phosphate and aluminum powder, the rare earth salt, the sodium fluosilicate and the sodium phosphate have a synergistic effect, and the advantages of sodium, phosphorus and rare earth elements are combined, so that the refining effect of crystalline silicon is optimal, the internal structure of the alloy is more uniform and compact, and the stability of the material is improved; the comprehensive mechanical property of the alloy material is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal preparation, and in particular to a GL80 silicon-aluminum alloy preparation process. Background Art

[0002] Silicon aluminum alloys are widely used in aerospace, automobile manufacturing, electronic equipment and other fields due to their excellent physical and mechanical properties.

[0003] However, there are many problems in the existing silicon aluminum alloy preparation process, such as uneven alloy composition, unstable mechanical properties, high production cost, complex process, etc. At present, the commonly used silicon aluminum alloy preparation methods mainly include melting casting, powder metallurgy and mechanical alloying. Although each has its own advantages, there are also obvious shortcomings. For example: the melting casting method is prone to component segregation and pore defects, resulting in unstable alloy performance, and the existing cast silicon aluminum alloy has coarse crystalline silicon structure and low density, which deteriorates the mechanical properties of the material. Summary of the invention

[0004] In order to refine the crystalline silicon structure in the silicon-aluminum alloy and improve the mechanical properties of the material in the silicon-aluminum alloy, the present application provides a GL80 silicon-aluminum alloy preparation process.

[0005] The present application provides a GL80 silicon aluminum alloy preparation process, which adopts the following technical solution: A GL80 silicon aluminum alloy preparation process comprises the following steps: (1) placing silicon powder and silicon aluminum alloy in a melting furnace, introducing nitrogen, heating to 900-1000° C., casting and molding, and remelting 2-3 times to obtain an alloy melt; (2) After the temperature of the alloy melt drops to 750-850°C, add a composite modifier of 20%-40% of the mass of the alloy melt, stir for 10-20 minutes, and keep warm for 1-2 hours to obtain a modified alloy liquid; (3) 1%-2% refining agent of the alloy melt is added to the modified alloy liquid, and the alloy is refined and impurities are removed for 20-30 minutes. After standing for 3-5 minutes, the scum on the surface of the melt is removed, and after the melt temperature drops to 620-660°C, it is poured into a preheated mold, and the silicon aluminum alloy material is obtained after cooling and demolding.

[0006] Preferably, the raw materials for preparing the composite modifier in step (2) include rare earth salt, sodium fluorosilicate, sodium phosphate and aluminum powder, and the weight ratio of the rare earth salt, sodium fluorosilicate, sodium phosphate and aluminum powder is (2-4): (5-7): (7-9): (80-86).

[0007] By adopting the above technical scheme, the present application adopts a smelting and casting process, melts the alloy raw material, performs a modification treatment, and then casts it. Among them, the silicon powder and the silicon-aluminum alloy are remelted 2-3 times, so that the silicon and aluminum in the alloy melt are fully mixed, which can reduce the uneven distribution of Si caused by segregation. The composite modifier is used for modification and stirring, and the primary silicon is refined; the composite modifier is made by mixing rare earth salts, sodium fluorosilicate, sodium phosphate and aluminum powder. Sodium and phosphorus have the effect of refining primary silicon, and rare earth salts have the effect of refining eutectic silicon. The synergistic effect of rare earth salts, sodium fluorosilicate and sodium phosphate combines the advantages of sodium, phosphorus and rare earth elements, so that the refinement effect of crystalline silicon is optimal, and then the irregularly shaped large-sized primary silicon is refined into uniform and fine particles, and the needle-shaped eutectic silicon is also transformed into fine particles or fibers, so that the internal structure of the alloy is more uniform and dense, so as to improve the stability of the material, which is conducive to improving the comprehensive mechanical properties of the alloy material.

[0008] Preferably, the rare earth salt is compounded from La salt, Yb salt and Ce salt, and the weight ratio of the La salt, Yb salt and Ce salt is (4-8): (3-5): (3-7).

[0009] Preferably, the La salt is lanthanum carbonate or lanthanum fluoride; the Yb salt is ytterbium fluoride; and the Ce salt is cerium fluoride.

[0010] By adopting the above technical solution, the rare earth salt in the composite modifier is compounded with La salt, Yb salt and Ce salt, which can achieve the best eutectic silicon refinement effect. When the composite modifier is heated to melt in the melt, a large number of La-Al, Yb-Al, and Ce-Al atomic clusters will be formed in the melt. When the eutectic silicon grows, these atomic clusters accumulate at the front of the solid-liquid interface, hindering the accumulation of Si atoms, thereby refining the large granular eutectic silicon modified by a small amount of rare earth elements into small granular particles. In addition, the enrichment of atomic clusters causes the solid-liquid interface to produce component supercooling, so that a small amount of eutectic silicon branches and grows into fine fibers, so that the material exhibits good mechanical properties.

[0011] Preferably, preparing the composite modifier into a master alloy comprises the following steps: First, rare earth salt, sodium fluorosilicate, sodium phosphate and aluminum powder are mixed evenly and dried, and ball-milled for 1-2 hours to obtain a mixed powder; then, the mixed powder is loaded into a mold, a pressure of 20-25MPa is applied, the pressure is maintained for 6-8 minutes, and sintered after demolding. The sintering temperature is 650-750°C. After keeping warm for 1-2 hours, the heating is stopped, and the composite modifier is obtained after cooling.

[0012] By adopting the above technical scheme, ball milling can achieve the best mixing effect and reduce the agglomeration between powders; applying pressure can make the powders more tightly bonded, which is conducive to the occurrence of subsequent reactions and the progress of mass transfer processes; during the sintering process of the master alloy, P will react with aluminum powder, resulting in the presence of pre-formed AlP compounds in the master alloy. After being added to the melt, the pre-formed AlP can directly serve as a heterogeneous nucleation core, increasing the number of nucleation cores in the alloy matrix and achieving the best modification and refinement effect. Sodium fluorosilicate can be preliminarily degassed, and heat is generated during the smelting process to form high temperatures, prompting aluminum elements to reduce rare earth salts to highly active atomic rare earth metals. This atomic rare earth metal can react with hydrogen at the smelting temperature to form hydrides, thereby achieving the purpose of solidifying hydrogen and removing hydrogen. In addition, rare earth elements and aluminum will form compounds that act as heterogeneous crystal nuclei to prevent the growth of eutectic silicon grains.

[0013] Preferably, the weight ratio of silicon powder to silicon aluminum alloy in step (1) is (0.5-1):10.

[0014] By adopting the above technical solution, increasing the silicon content in the silicon-aluminum alloy can significantly reduce the density and thermal expansion coefficient of the alloy material.

[0015] Preferably, in the silicon-aluminum alloy in step (1), Si accounts for 80% of the total mass of the silicon-aluminum alloy, and Al accounts for 14%-16% of the total mass of the silicon-aluminum alloy.

[0016] By adopting the above technical solution, the appropriate ratio of silicon and aluminum in the silicon-aluminum alloy of step (1) has better alloy processing performance.

[0017] Preferably, the rotation speed of the graphite rotor in step (2) is 300-400 r / min.

[0018] By adopting the above technical solution, the rotation speed of the graphite rotor is 300-400r / min, which can achieve the best crystalline silicon refinement effect.

[0019] Preferably, the refining agent in step (3) is one or more of sodium chloride, calcium carbonate, sodium hexafluoroaluminate, and sodium thiosulfate.

[0020] By adopting the above technical solution, the effective ingredients in the refining agent can react with impurities in the alloy liquid to generate salt compounds with lower density, which float to the surface of the alloy liquid and are removed, while reducing the hydrogen content in the alloy melt and improving the degassing effect.

[0021] This application has the following beneficial effects: In the present application, the present application adopts a smelting and casting process, and the alloy raw material is melted and then subjected to a modification treatment, and then cast and molded. Among them, the silicon powder and the silicon-aluminum alloy are remelted 2-3 times, so that the silicon and aluminum in the alloy melt are fully mixed, which can reduce the uneven distribution of Si caused by segregation. The composite modifier is used for modification and stirring, and the primary silicon is refined; the composite modifier is made by mixing rare earth salts, sodium fluorosilicate, sodium phosphate and aluminum powder. Sodium and phosphorus both have the effect of refining primary silicon, and rare earth salts have the effect of refining eutectic silicon. The rare earth salts, sodium fluorosilicate and sodium phosphate work synergistically, combining the advantages of sodium, phosphorus and rare earth elements, so that the refinement effect of crystalline silicon is optimal, and then the irregularly shaped large-sized primary silicon is refined into uniform and fine particles, and the needle-shaped eutectic silicon is also transformed into fine particles or fibers, so that the internal structure of the alloy is more uniform and dense, so as to improve the stability of the material, which is conducive to improving the comprehensive mechanical properties of the alloy material. DETAILED DESCRIPTION

[0022] Preparation Example Preparation Example 1 Preparation of composite modifier: First, 2g of rare earth salt (0.8g of lanthanum carbonate, 0.6g of ytterbium fluoride, and 0.6g of cerium fluoride), 5g of sodium fluorosilicate, 7g of sodium phosphate and 86g of aluminum powder were mixed evenly and dried, and ball-milled for 1h to obtain a mixed powder; then, the mixed powder was loaded into a mold, a pressure of 20MPa was applied, the pressure was maintained for 6min, and the mold was demolded and sintered at a sintering temperature of 650°C. After keeping warm for 1h, heating was stopped and the composite modifier was obtained after cooling.

[0023] Preparation Example 2 Preparation of composite modifier: First, 3g of rare earth salt (1.2g of lanthanum fluoride, 0.8g of ytterbium fluoride, and 1g of cerium fluoride), 6g of sodium fluorosilicate, 8g of sodium phosphate and 83g of aluminum powder were mixed evenly and dried, and ball-milled for 1.5h to obtain a mixed powder; then, the mixed powder was loaded into a mold, a pressure of 25MPa was applied, the pressure was maintained for 8min, and the mold was demolded and sintered at a sintering temperature of 700°C. After keeping warm for 1.5h, the heating was stopped and the composite modifier was obtained after cooling.

[0024] Preparation Example 3 Preparation of composite modifier: First, 4g of rare earth salt (1.6g of lanthanum fluoride, 1g of ytterbium fluoride, 1.4g of cerium fluoride), 7g of sodium fluorosilicate, 9g of sodium phosphate and 80g of aluminum powder were mixed evenly and dried, and ball-milled for 2h to obtain a mixed powder; then, the mixed powder was loaded into a mold, a pressure of 25MPa was applied, the pressure was maintained for 8min, and the mold was demolded and sintered at a sintering temperature of 750°C. After keeping warm for 2h, the heating was stopped and the composite modifier was obtained after cooling.

[0025] Preparation Example 4 The difference between this preparation example and preparation example 2 is that an equal amount of ScF3 is used to replace lanthanum fluoride in the rare earth salt.

[0026] Preparation Example 5 The difference between this preparation example and preparation example 2 is that an equal amount of ScF3 is used to replace the cerium fluoride in the rare earth salt.

[0027] Preparation Example 6 The difference between this preparation example and preparation example 2 is that the rare earth salt is compounded by lanthanum fluoride and ytterbium fluoride, that is, no cerium fluoride is added.

[0028] Preparation Example 7 The difference between this preparation example and preparation example 2 is that lanthanum fluoride is used as the rare earth salt, that is, ytterbium fluoride and cerium fluoride are not added. Example

[0029] Example 1 A GL80 silicon aluminum alloy preparation process comprises the following steps: (1) 5 g of silicon powder and 100 g of silicon aluminum alloy (Jiangsu Huaneng GL80) were placed in a melting furnace, nitrogen was introduced, and the mixture was heated to 900° C. After casting, the mixture was remelted twice to obtain an alloy melt; (2) After the temperature of the alloy melt drops to 750°C, add 24 g of a composite modifier (prepared in Preparation Example 1) into the alloy melt, stir for 10 min, and keep warm for 1 h to obtain a modified alloy liquid; (3) 0.6 g of sodium chloride and 0.6 g of calcium carbonate were added to the modified alloy liquid, and the alloy was refined and impurity-removed for 20 min. After standing for 3 min, the scum on the surface of the melt was removed. After the melt temperature dropped to 620 °C, the melt was poured into a preheated mold, and the silicon-aluminum alloy material was obtained after cooling and demolding.

[0030] Example 2 A GL80 silicon aluminum alloy preparation process comprises the following steps: (1) 7 g of silicon powder and 100 g of silicon aluminum alloy (Jiangsu Huaneng GL80) were placed in a melting furnace, nitrogen was introduced, and the mixture was heated to 950° C. After casting, the mixture was remelted three times to obtain an alloy melt; (2) After the temperature of the alloy melt drops to 800°C, 39 g of a composite modifier (prepared in Preparation Example 2) is added, stirred for 15 min, and kept warm for 2 h to obtain a modified alloy liquid; (3) 1.3 g of sodium hexafluoroaluminate and 1.3 g of calcium carbonate were added to the modified alloy liquid, refined and impurity removed for 25 min, and after standing for 4 min, the scum on the surface of the melt was removed. After the melt temperature dropped to 640 ° C, it was poured into a preheated mold and cooled and demolded to obtain a silicon aluminum alloy material.

[0031] Example 3 A GL80 silicon aluminum alloy preparation process comprises the following steps: (1) 10 g of silicon powder and 100 g of silicon aluminum alloy (Jiangsu Huaneng GL80) were placed in a melting furnace, nitrogen was introduced, and the mixture was heated to 1000° C. After casting, the mixture was remelted three times to obtain an alloy melt; (2) After the temperature of the alloy melt drops to 850°C, 56 g of a composite modifier (prepared in Preparation Example 3) is added, stirred for 20 min, and kept warm for 2 h to obtain a modified alloy liquid; (3) 0.7 g of sodium thiosulfate and 0.7 g of calcium carbonate were added to the modified alloy liquid, and the alloy was refined and impurities were removed for 30 min. After standing for 5 min, the scum on the surface of the melt was removed. After the melt temperature dropped to 660 ° C, it was poured into a preheated mold, and the silicon aluminum alloy material was obtained after cooling and demolding.

[0032] Example 4 The difference between this embodiment and embodiment 2 is that the composite modifier in step (2) is the composite modifier prepared in preparation example 4.

[0033] Example 5 The difference between this embodiment and embodiment 2 is that the composite modifier in step (2) is the composite modifier prepared in preparation example 5.

[0034] Example 6 The difference between this embodiment and embodiment 2 is that the composite modifier in step (2) is the composite modifier prepared in preparation example 6.

[0035] Example 7 The difference between this embodiment and embodiment 2 is that the composite modifier in step (2) is the composite modifier prepared in preparation example 7.

[0036] Comparative Example Comparative Example 1 A GL80 silicon aluminum alloy preparation process, which differs from Example 2 in that the composite modifier in step (2) is replaced by an equal amount of a single modifier. The preparation method of the single modifier is as follows: First, 3 g of lanthanum fluoride and 83 g of aluminum powder were mixed evenly and dried, and ball-milled for 1.5 hours to obtain a mixed powder; then, the mixed powder was loaded into a mold, a pressure of 25 MPa was applied, and the pressure was maintained for 8 minutes. After demolding, sintering was performed at a sintering temperature of 700°C. After keeping warm for 1.5 hours, heating was stopped, and a single modifier was obtained after cooling.

[0037] Comparative Example 2 A GL80 silicon aluminum alloy preparation process, which differs from Example 2 in that the composite modifier in step (2) is replaced by an equal amount of a single modifier. The preparation method of the single modifier is as follows: First, 3g of sodium fluorosilicate and 83g of aluminum powder were mixed evenly and dried, and ball-milled for 1.5h to obtain a mixed powder; then, the mixed powder was loaded into a mold, a pressure of 25MPa was applied, the pressure was maintained for 8min, and the mold was demolded and sintered at a sintering temperature of 700℃. After keeping warm for 1.5h, the heating was stopped and a single modifier was obtained after cooling.

[0038] Comparative Example 3 A GL80 silicon aluminum alloy preparation process, which differs from Example 2 in that no composite modifier is added in step (2).

[0039] Comparative Example 4 A GL80 silicon aluminum alloy preparation process, which differs from Example 2 in that step (1) is modified as follows: (1) 7 g of silicon powder and 100 g of silicon aluminum alloy (Jiangsu Huadian GL80) are placed in a melting furnace, nitrogen is introduced, and the mixture is heated to 950° C. to obtain an alloy melt.

[0040] Comparative Example 5 A GL80 silicon aluminum alloy preparation process, which differs from Example 2 in that step (2) is modified as follows: (2) after the alloy melt temperature drops to 800°C, 39g of a composite modifier (prepared in Preparation Example 2) is added, and the temperature is kept for 2h to obtain a modified alloy liquid.

[0041] Performance testing 1. Tensile performance test: According to GB / T 228.1-2021 standard, a universal tensile testing machine was used to test the tensile strength, yield strength and elongation of the samples in Examples 1-7 and Comparative Examples 1-5, and the tensile rate was 1 mm / min. When calculating the elongation of the sample, mark a section of the sample gauge as long as possible, mark at both ends of the sample gauge, and measure the marked length L0 with a vernier caliper. After breaking, splice the fracture of the sample and measure the marked length L1 again. Each measurement should be repeated three times, and the average of the three measurement data is taken. The calculation formula for elongation δ (1): 2. Hardness test: The Vickers hardness test was conducted using a HVS-1000Z Vickers hardness tester. Under a load of 200 g, a diamond quadrangular pyramid indenter was pressed into the surface of the alloy to be tested. The load was maintained for 10 seconds, and then the diagonal of the prism indentation was measured using a digital micrometer eyepiece to obtain the Vickers hardness value, and the data was recorded in Table 1.

[0042] 3. Density measurement: The density was measured using the Archimedean displacement method and the data are recorded in Table 1.

[0043] Table 1 According to Example 2 and Example 4-5 and combined with the data in Table 1, it can be seen that the composite modifier formed by compounding La salt, Yb salt and Ce salt with aluminum powder has a good modification effect, while the modification effect of Sc salt is poor. Among them, La salt, Yb salt and Ce salt form La-Al, Yb-Al, Ce-Al atomic clusters with aluminum powder. These atomic clusters accumulate at the front of the solid-liquid interface when eutectic silicon grows, hindering the accumulation of Si atoms, thereby refining the large granular eutectic silicon modified by a small amount of rare earth elements into small granular or fibrous pieces, reducing the size of eutectic silicon, reducing the pores in the alloy material, thereby reducing the formation of cracks, and making the silicon-aluminum alloy material show good mechanical properties.

[0044] According to Example 2 and Example 6-7 and combined with the data in Table 1, it can be seen that the composite modifier formed by compounding La salt, Yb salt and Ce salt with aluminum powder has a good modification effect. If any one or two rare earth salts are missing, the modification effect of the composite modifier is limited, and the uniformity of the internal structure of the alloy material is poor. Among them, La salt, Yb salt and Ce salt will form compounds with aluminum to act as heterogeneous crystal nuclei, prevent the growth of eutectic silicon grains, make the internal structure of the alloy more uniform and dense, so as to improve the stability of the material, which is beneficial to improve the comprehensive mechanical properties of the alloy material and extend the service life of the material.

[0045] According to Example 2 and Comparative Examples 1-2 and combined with the data in Table 1, it can be seen that the modification effect of using a single modifier is not ideal, while using a combination of multiple modifiers will not affect each other, and rare earth salts can extend the effective time of sodium phosphate modification. The surface activity of rare earth elements is very strong and they are easy to accumulate on the existing interface in the melt. This enrichment will hinder the enrichment of Si atomic groups, and also hinder the growth of primary silicon in the solidified structure. It can simultaneously refine the primary silicon and eutectic silicon, so that the mechanical properties of the material are significantly improved.

[0046] According to Example 2 and Comparative Example 3 and combined with the data in Table 1, it can be seen that the mechanical properties of silicon-aluminum alloy can be improved by using a composite modifier to perform a modification treatment on the silicon-aluminum alloy. Among them, the rare earth salt, sodium fluorosilicate and sodium phosphate work synergistically, combining the advantages of sodium, phosphorus and rare earth elements, so that the refinement effect of crystalline silicon is optimal, and the irregularly shaped large-sized primary silicon is refined into uniform and fine particles, while the needle-like eutectic silicon is also transformed into fine particles or fibers. The prepared silicon-aluminum alloy material has a higher density, so that the strength of the silicon-aluminum alloy material is higher.

[0047] According to Example 2 and Comparative Examples 4-5 and in combination with the data in Table 1, it can be seen that: in the preparation process of silicon-aluminum alloy, remelting the raw materials multiple times can make the silicon and aluminum in the melt fully mixed, which can reduce the uneven distribution of Si caused by segregation; and stirring can further refine the primary silicon and eutectic silicon and increase the density of the material.

[0048] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A GL80 silicon aluminum alloy preparation process, characterized in that: The preparation process of the silicon aluminum alloy comprises the following steps: (1) Place silicon powder and silicon aluminum alloy in a melting furnace, introduce nitrogen, heat to 900-1000°C, cast and shape, and remelt 2-3 times to obtain an alloy melt; (2) After the temperature of the alloy melt drops to 750-850°C, add a composite modifier of 20%-40% of the mass of the alloy melt, stir for 10-20 minutes, and keep warm for 1-2 hours to obtain a modified alloy liquid; (3) Add 1%-2% refining agent to the modified alloy liquid, refine and remove impurities for 20-30 minutes, let it stand for 3-5 minutes, remove the scum on the surface of the melt, and after the melt temperature drops to 620-660℃, pour it into a preheated mold, cool and demold it to obtain the silicon aluminum alloy material.

2. A GL80 silicon aluminum alloy preparation process according to claim 1, characterized in that: The raw materials for preparing the composite modifier in step (2) include rare earth salt, sodium fluorosilicate, sodium phosphate and aluminum powder, and the weight ratio of the rare earth salt, sodium fluorosilicate, sodium phosphate and aluminum powder is (2-4): (5-7): (7-9): (80-86).

3. A GL80 silicon aluminum alloy preparation process according to claim 2, characterized in that: The rare earth salt is compounded from La salt, Yb salt and Ce salt, and the weight ratio of the La salt, Yb salt and Ce salt is (4-8): (3-5): (3-7).

4. A GL80 silicon aluminum alloy preparation process according to claim 3, characterized in that: The La salt is one of lanthanum carbonate and lanthanum fluoride; the Yb salt is ytterbium fluoride; and the Ce salt is cerium fluoride.

5. A GL80 silicon aluminum alloy preparation process according to claim 2, characterized in that: The composite modifier is prepared into a master alloy, comprising the following steps: First, rare earth salt, sodium fluorosilicate, sodium phosphate and aluminum powder are mixed evenly and dried, and ball-milled for 1-2 hours to obtain a mixed powder; then, the mixed powder is loaded into a mold, a pressure of 20-25MPa is applied, the pressure is maintained for 6-8 minutes, and sintered after demolding. The sintering temperature is 650-750°C. After keeping warm for 1-2 hours, the heating is stopped, and the composite modifier is obtained after cooling.

6. A GL80 silicon aluminum alloy preparation process according to claim 1, characterized in that: In the step (1), the weight ratio of silicon powder to silicon aluminum alloy is (0.5-1):

10.

7. A GL80 silicon aluminum alloy preparation process according to claim 1, characterized in that: In the silicon-aluminum alloy in step (1), Si accounts for 80% of the total mass of the silicon-aluminum alloy, and Al accounts for 14%-16% of the total mass of the silicon-aluminum alloy.

8. A GL80 silicon aluminum alloy preparation process according to claim 1, characterized in that: In the step (2), the rotation speed of the graphite rotor is 300-400 r / min.

9. A GL80 silicon aluminum alloy preparation process according to claim 1, characterized in that: The refining agent in step (3) is one or more of sodium chloride, calcium carbonate, sodium hexafluoroaluminate, and sodium thiosulfate.